Efficacy of probiotic supplementation on growth performance and carcass traits in Japanese quails - AYASAN, TUGAY (The Indian Journal of Animal Sciences, 2016)
This study aimed to evaluate the effects of probiotics on fattening performance and carcass parameters in 1– to 35–day-old Japanese quails. Day-old male Japanese quail chicks (288) were randomly divided into 4 treatments with 3 replicates of 24 / pen (mean body weight 8.39 g). The dietary treatments were as follows: Group A, basal diet; group B, basal diet supplemented with 0.5 kg/tonne protexin; group C, basal diet supplemented with 1.0 kg/ tonne protexin; and group D, basal diet supplemented with 1.5 kg/tonne protexin. The study lasted for 5 weeks. Results showed that probiotic did not influence body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR), and carcass traits of 35–d-old broilers (P> 0.05). Inclusion of 1.5 kg/tonne probiotic in the diet of quails decreased average weekly body weights, compared with those fed with basal diet and another groups (P< 0.05).